TI_GERICHTE 52.2017.178 vom 14. Februar 2017 , Licenza edilizia per la costruzione di uno stabile d'appartamenti - TI Tribunale d'appello (2017)
Licenza edilizia per la costruzione di uno stabile d'appartamenti